Human platelet lysate: Replacing fetal bovine serum as a gold standard for human cell propagation?. (January 2016) - Burnouf, Thierry; Strunk, Dirk; Koh, Mickey B.C.; Schallmoser, Katharina
Abstract: The essential physiological role of platelets in wound healing and tissue repair builds the rationale for the use of human platelet derivatives in regenerative medicine. Abundant growth factors and cytokines stored in platelet granules can be naturally released by thrombin activation and clotting or artificially by freeze/thaw-mediated platelet lysis, sonication or chemical treatment. Human platelet lysate prepared by the various release strategies has been established as a suitable alternative to fetal bovine serum as culture medium supplement, enabling efficient propagation of human cells under animal serum-free conditions for a multiplicity of applications in advanced somatic cell therapy and tissue engineering. The rapidly increasing number of studies using platelet derived products for inducing human cell proliferation and differentiation has also uncovered a considerable variability of human platelet lysate preparations which limits comparability of results. The main variations discussed herein encompass aspects of donor selection, preparation of the starting material, the possibility for pooling in plasma or additive solution, the implementation of pathogen inactivation and consideration of ABO blood groups, all of which can influence applicability. This review outlines the current knowledge about human platelet lysate as a powerful additive for human cell propagation and highlights its role as a prevailing supplement for human cell culture capable to replace animal serum in a growing spectrum of applications.